1999
DOI: 10.1007/pl00012137
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile-adult distribution of the bivalve Mya arenaria on intertidal flats in the Wadden Sea: why are there so few year classes?

Abstract: Patchy distribution is frequently observed in benthic marine invertebrates. In order to indentify factors causing spatial patterns in the bivalve Mya arenaria, abundances of juveniles and adults, as well as death assemblages, were recorded on a 20-km scale in the intertidal zone of the Sylt-Rømø Bight. Both adults and juveniles exhibited pronounced patchiness. Shell length of juveniles rarely exceeded 2 mm in 1995, which was most likely a consequence of epibenthic predators truncating the size spectrum. Only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…The maximum density of juveniles recorded in the study site is within the range reported by other authors in northern European populations (van der Veer et al, 1998;Strasser et al, 1999;Strasser and Gunter, 2001). …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The maximum density of juveniles recorded in the study site is within the range reported by other authors in northern European populations (van der Veer et al, 1998;Strasser et al, 1999;Strasser and Gunter, 2001). …”
Section: Discussionsupporting
confidence: 88%
“…A plausible explanation is that settlement depends on local hydrodynamics, as pointed out by other authors (Armonies, 1996;Hunt and Mullineaux, 2002). Therefore, the aggregation of juveniles may be observed in different levels of the intertidal region (Emerson and Grant, 1991;Strasser et al, 1999) depending on the dominant current regime. However, the distribution process of Mya arenaria juveniles may also depend to some extent on the active role of the species, which is suggested by the juveniles of the invasive clam avoiding the excavated plots.…”
Section: Discussionmentioning
confidence: 78%
“…Predominance of a single generation in local M. arenaria populations was also reported from the Wadden Sea (Strasser et al 1999). A number of studies demonstrated drastic (Smidt 1944;Goshima 1982) as well as cyclic (Glude 1954;Commito 1982;Sadykhova 1982) changes in the population structure of this species in different parts of its geographical range.…”
Section: Discussionmentioning
confidence: 77%
“…However, to assume that successful recruitment of soft-shell clams is only possible when the number of older specimens is low would probably oversimplify the mechanisms of population dynamics. There is a lot of data available about a lack of correlation between the number of spat and number of adult specimens in M. arenaria local populations (Kühl 1955;Brousseau and Baglivo 1988;Günter 1992;Strasser et al 1999). The obvious synchrony of M. arenaria bed dynamics in both investigated habitats suggests the existence of a common mechanism regulating recruitment rate and periodicity in these areas.…”
Section: Discussionmentioning
confidence: 97%
“…To date, little or no disease or pathogens have been reported in Mya arenaria on European shores (Strasser et al, 1999), in contrast to the number of diseases and parasites being present in the more intensively cultured M. arenaria populations of North America. No parasites, pathogenic states or disease were found in any of the soft shell clams sampled in either of the two sites in the current study, despite a heavy prevalence of trematodes, neoplasia and Nematopsis spp.…”
Section: Discussionmentioning
confidence: 99%